Judy Quinn & Emily Lethbridge (eds.), Creating the Medieval Saga. Versions, Variability and Editorial Interpretations of Old Norse Saga Literature - Edlund, Lars-Erik (Journal of Northern Studies, 2012)
Review of: Judy Quinn & Emily Lethbridge (eds.), Creating the Medieval Saga. Versions, Variability and Editorial Interpretations of Old Norse Saga Literature (The Viking Collection. Studies in Northern Civilization. General editors: Margaret Clunies Ross, Matthew Driscoll & Mats Malm. Vol. 18), Odense: University Press of Southern Denmark 2010, ISBN 9788776745325; ISSN 01088408, 337 pp.